Can we live without trees? a book about trees - Papa, May Tobias; Alvarez, Fran (Quezon City Adarna House, Inc., 2014)
"Here is a reference book about how important trees are to humans and to all living things, how biologically diverse the Philippine is, and how we can help save our forests."
This book is recommended for children ages 9 and above.
Keywords: Trees -- Juvenile literature